Search for Dark Matter Produced in Association with a Dark Higgs Boson Decaying into W±W∓ or ZZ in Fully Hadronic Final States from √s=13 TeV pp Collisions Recorded with the ATLAS Detector - Alonso, Francisco (2021)
Several extensions of the Standard Model predict the production of dark matter particles at the LHC. An uncharted signature of dark matter particles produced in association with V V = W ± W ∓ or Z Z pairs from a decay of a dark Higgs boson s is searched for using 139 fb − 1 of pp collisions recorded by the ATLAS detector at a center-of-mass energy of 13 TeV. The s → V (q ¯ q) V (q ¯ q) decays are reconstructed with a novel technique aimed at resolving the dense topology from boosted V V pairs using jets in the calorimeter and tracking information. Dark Higgs scenarios with m s > 160 GeV are excluded.